Volodymyr Petrovych Filatov, an outstanding ophthalmologist, Academician of the AS of UkrSSR and AMS of USSR, and the founder of the Ukrainian ophthalmology school: a life pathway (Ukrainian Journal of Ophthalmology, 2025)
Volodymyr Petrovych Filatov, an outstanding ophthalmologist, Academician of the AS of UkrSSR and AMS of USSR, and the founder of the Ukrainian ophthalmology school: a life pathway